Immune profiling identifies CD161+CD127+CD8+ T cells as a predictive biomarker for Anti-PD-L1 therapy response in the SCLC-I subtype - Jingjing Qu; Wenjia Sun; Yuekang Li; Ziwan Cai; Binggen Wu; Qian Shen; Lijun Chen; Bo Wang; Lixiong Ying; Chenchai Xie; Jing Zheng; Jianya Zhou; et al. (Journal of Translational Medicine)
Abstract Background Advances in molecular subtype classification have improved the understanding of extensive-stage small cell lung cancer (ES-SCLC). However, immune landscape differences across ES-SCLC subtypes remain poorly defined. This study aimed to characterize ES-SCLC immune profiles and explore their association with response to immunotherapy. Methods Tumor samples from 135 patients with ES-SCLC were analyzed for molecular subtyping using immunohistochemical markers. Immune profiling of peripheral blood mononuclear cells was performed using cytometry by time-of-flight (CyTOF) and flow cytometry, and tumor tissues were assessed through multiplex immunofluorescence for immune cell subset characterization and distribution. Results Molecular subtyping of the 135 ES-SCLC cases identified 54.1%, 20.0%, 7.4%, and 18.5% as ASCL1-dominant, NEUROD1-dominant, POU2F3-dominant, and inflamed SCLC-I subtypes, respectively. CyTOF indicated a distinct enrichment of CD161+CD127+CD8+T cells in SCLC-I,with flow cytometry validating significantly higher proportions. These cells exhibited elevated cytotoxic markers (GZMB and GNLY) and reduced exhaustion markers (PD-1, TIGIT, and LAG-3) compared with those of other subtypes(P < 0.05). Multiplex immunofluorescence confirmed higher intratumoral infiltration of CD161+CD127+CD8+ T cells in SCLC-I. The intratumoral and peripheral levels of this subset were strongly correlated(r = 0.669, P < 0.0001). Patients with a CD161+CD127+CD8+ T/CD8+ T cell ratio of ≥ 2.7% had a significantly prolonged progression-free survival (PFS, 11.0 vs. 7.0 months, P = 0.0196). Conclusions The SCLC-I subtype exhibited a distinct immune profile characterized by enrichment of CD161+CD127+CD8+ T cells in both peripheral blood and tumor tissue, which was associated with PFS following anti–PD-L1 therapy. These findings highlight the significance of subtype-specific immune profiling and the potential of CD161+CD127+CD8+ T cells as a predictive biomarker to guide precision immunotherapy in ES-SCLC.